PLURALISME AGAMA DALAM BUDDHISME (IAIN Kediri, 2015)
In Indonesia, religious pluralism remains a heated debate in Indonesia where pros and cons are dominated by whether it is compatible with Islam or not. There is still less discussion in regard with other religions. This paper attempts to explain the concept of religious pluralism in Buddhism, focusing on the fundamental issues such as truth claim, relation with other religions, as well as religious dialogue. It found out that Buddhism suggests a moderate way of religious pluralism which is based on â€œcritical-toleranceâ€. It also accepts that all other religions are true but are not the right paths toward enlightment.Keywords: Â Buddhism, religious pluralism, critical tolerance